(untitled) (Papeles, 2017)
This article reports a qualitative action research study on the contribution of using songs and lyrics to integrate cultural understanding and language development in an English as a foreign language (EFL) class at a middle school. We observed that our learners had difficulty to understand and express themselves in English. The social and cultural context of the late 1960’s Hippie movement was the subject of the study through songs and lyrics. We offer our readers the most relevant literature and a synthesis of research reports on the subject to invite them to deepen in this topic. The findings of this qualitative study suggest that culture contextualized language and enhanced comprehension facilitates oral expression in EFL.